Toner

The toner composition, with its domain matrix structure of crystalline and amorphous resins, addresses the challenges of low-temperature fixing, high gloss, and abrasion resistance, providing a superior performance in toner applications.

JP2025065738APending Publication Date: 2025-04-22CANON KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023175142
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Toner formulations containing crystalline resins face challenges in achieving low-temperature fixing while maintaining high gloss and abrasion resistance, particularly when exposed to eraser rubbing.

Method used

A toner composition featuring toner particles with a domain matrix structure, where the matrix is composed of crystalline resin A and the domains contain amorphous resin B, with specific size and distribution criteria for domains C and D to optimize low-temperature fixing, gloss retention, and eraser resistance.

Benefits of technology

The proposed toner achieves excellent low-temperature fixing properties, high gloss over a wide temperature range, and enhanced abrasion resistance during low-temperature fixing, effectively addressing the limitations of prior toner technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065738000001
    Figure 2025065738000001
  • Figure 2025065738000002
    Figure 2025065738000002
  • Figure 2025065738000003
    Figure 2025065738000003
Patent Text Reader

Abstract

To provide a toner excellent in low-temperature fixability and high glossiness in a wider temperature region, and also excellent in scratch resistance at a low-temperature fixation.SOLUTION: A toner includes toner particles. The toner has a weight average particle diameter within a prescribed range. When a cross section of the toner is observed, a domain-matrix structure is seen in which domains are dispersed in a matrix. The matrix includes a crystalline resin A. Each of the domains includes an amorphous resin B. If a domain whose major axis is 300 nm or more is domain C and a domain whose major axis is 200 nm or less is domain D, a number average major axis of the domains D is 30 to 150 nm, and a ratio of the cross sections simultaneously satisfying (i) and (ii) is 90 domain% or more: (i) 5 to 20 domains C are present per cross section, and an area ratio of the domains C is 10 to 30 area%; and (ii) the domains D can be observed across a whole area in the cross section.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to toners used in electrophotography and electrostatic recording. [Background technology]

[0002] Conventionally, energy saving has been considered as a major technical issue in electrophotographic devices, and a significant reduction in the amount of heat required for fixing devices has been considered. In particular, there is an increasing need for toners that can be fixed with less energy, that is, so-called "low-temperature fixing properties." Moreover, in recent years, there has been a demand for scratch resistance caused by erasers in order to prevent the printed characters from being erased or tampered with.

[0003] As a method for enabling fixing at low temperatures, Patent Document 1 considers a toner containing a plasticizer. The plasticizer has the effect of accelerating the softening speed of the binder resin while maintaining the glass transition temperature (Tg) of the toner, and can improve low-temperature fixing properties. However, since the toner softens through a step of plasticizing the binder resin after the plasticizer melts, there is a limit to the melting speed of the toner, and further improvement in low-temperature fixing properties is desired. Therefore, a method of using a crystalline resin as a binder resin is being considered. Amorphous resins that are generally used as binder resins for toners do not show a clear endothermic peak in differential scanning calorimetry (DSC) measurements, but if they contain a crystalline resin component, an endothermic peak (melting point) appears in DSC measurements.

[0004] Crystalline resins have the property that they hardly soften at temperatures lower than their melting point because their molecular chains are regularly arranged. Furthermore, when the temperature exceeds the melting point, the crystals melt suddenly, which causes a sudden drop in viscosity. For this reason, crystalline resins are attracting attention as materials that have excellent sharp melt properties and low-temperature fixing properties. As the crystalline resin, there is a toner using a crystalline vinyl resin having a long-chain alkyl group in a side chain in the molecule. Usually, a crystalline vinyl resin has a long-chain alkyl group as a side chain in the main chain skeleton, and the long-chain alkyl groups in the side chain crystallize with each other to become a crystalline resin. Patent Document 2 and Patent Document 3 propose a toner having a domain matrix structure having a matrix containing a crystalline vinyl resin and a domain containing an amorphous resin. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2013 / 047296 [Patent Document 2] JP 2014-142632 A [Patent Document 3] Patent Publication No. 2022-144501 Summary of the Invention [Problem to be solved by the invention]

[0006] On the other hand, the present inventors have recognized that toners containing crystalline resins generally have a problem of low eraser abrasion resistance. Crystalline resins have a lower polarity than commonly used binder resins for toners, and therefore have a low affinity with paper mainly composed of cellulose. Therefore, in a test to check the abrasion resistance under a certain pressure such as rubbing with an eraser, it is considered that the toners are likely to peel off. Although the toners described in Patent Documents 2 and 3 have excellent low-temperature fixing properties, there is still room for improvement in terms of eraser abrasion resistance during low-temperature fixing.

[0007] In addition, the domain containing the amorphous resin has a relatively slower melting speed than the matrix containing the crystalline resin during low-temperature fixing. The domain size is large, and fine irregularities occur on the surface of the fixed image during low-temperature fixing, which tends to reduce gloss. Therefore, further improvements are required to realize a toner that is excellent in low-temperature fixing property and high gloss over a wide temperature range, and further has excellent eraser abrasion resistance during low-temperature fixing.

[0008] The present disclosure is directed to a toner that is excellent in low-temperature fixing property and high gloss over a wide temperature range, and further has excellent eraser abrasion resistance during low-temperature fixing. [Means for solving the problem]

[0009] The present disclosure relates to a toner having toner particles containing a crystalline resin A and an amorphous resin B, The toner has a weight average particle size of 4.0 to 10.0 μm, When the cross section of the toner was observed using a scanning transmission electron microscope, A domain matrix structure in which domains are dispersed in a matrix is ​​observed in the cross section, The matrix contains the crystalline resin A, The domain contains the amorphous resin B, (a) when the domains having a major axis of 300 nm or more are called domains C and the domains having a major axis of 200 nm or less are called domains D, the number-average major axis of the domains D is 30 to 150 nm, (b) The proportion of the cross sections that satisfy both the following (i) and (ii) is 90% or more by number: (i) 5 to 20 domains C are present per cross section of one toner particle, and the area ratio of the domains C is 10 to 30 area % based on the area of ​​the cross section; (ii) the domain D is observed over the entire area of ​​the cross section except for the domain C; Regarding toner. Effect of the Invention

[0010] According to the present disclosure, it is possible to provide a toner that is excellent in low-temperature fixability and high gloss over a wide temperature range, and further has excellent abrasion resistance during low-temperature fixation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In the present disclosure, the description of a numerical range such as "XX or more and YY or less" or "XX to YY" means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. The (meth)acrylic acid ester means an acrylic acid ester and / or a methacrylic acid ester.

[0012] In addition, in the present disclosure, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ. The term "monomer unit" refers to the reacted form of a monomer substance in a polymer. For example, one section of carbon-carbon bond in the main chain of a polymer in which a vinyl monomer is polymerized is considered to be one unit. A vinyl monomer can be represented by the following formula (6). [ka]

[0013] In formula (6), R A represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group); R B represents an optional substituent. In the present disclosure, a crystalline resin refers to a resin that shows a clear endothermic peak in a differential scanning calorimeter (DSC) measurement.

[0014] The present inventors have found, when observing a cross section of a toner, that in a toner having a domain matrix structure having a matrix containing a crystalline resin and domains containing an amorphous resin, the above-mentioned problems can be solved by appropriately controlling the size, number and area of ​​the large and small domains.

[0015] The present disclosure relates to a toner having toner particles containing a crystalline resin A and an amorphous resin B, The toner has a weight average particle size of 4.0 to 10.0 μm, When the cross section of the toner was observed using a scanning transmission electron microscope, A domain matrix structure in which domains are dispersed in a matrix is ​​observed in the cross section, The matrix contains the crystalline resin A, The domain contains the amorphous resin B, (a) when the domains having a major axis of 300 nm or more are called domains C and the domains having a major axis of 200 nm or less are called domains D, the number-average major axis of the domains D is 30 to 150 nm, (b) The proportion of the cross sections that satisfy both the following (i) and (ii) is 90% or more by number: (i) 5 to 20 domains C are present per cross section of one toner particle, and the area ratio of the domains C is 10 to 30 area % based on the area of ​​the cross section; (ii) the domain D is observed over the entire area of ​​the cross section except for the domain C; Regarding toner.

[0016] In cross-sectional observation of the toner, excellent low-temperature fixability can be obtained by providing a domain matrix structure formed by a matrix containing crystalline resin A and a domain containing amorphous resin B. If there is no domain matrix structure and crystalline resin A and amorphous resin B are compatible to form a uniform structure, the sharp melting property of the crystalline resin tends to decrease, and low-temperature fixability tends to decrease.

[0017] Generally, crystalline resins have a high melting speed. Therefore, during low-temperature fixing, a speed difference occurs between the crystalline resin and the amorphous resin, which has a relatively slow melting speed. As a result, the fixing ends before the amorphous resin is completely melted, causing minute irregularities in the fixed image due to insufficiently melted amorphous resin, which can reduce gloss. Therefore, in order to achieve high gloss during low-temperature fixing, the domains containing amorphous resin B must be relatively small. Therefore, with regard to (a), the number-average major axis of domain D is 150 nm or less.

[0018] On the other hand, at higher fixing temperatures, the amorphous resin with small domains can melt sufficiently and penetrates too much into the gaps in the paper together with the crystalline resin, which can cause the paper unevenness to be affected. This may result in a decrease in gloss. Therefore, in order to achieve high gloss during fixing at a higher temperature, the domains containing the amorphous resin B must be relatively large. Therefore, with regard to (a), the number-average major axis of the domains D is 30 nm or more.

[0019] In addition, as mentioned above, crystalline resins with low affinity to paper have a problem of poor eraser abrasion resistance. Therefore, it is important to control the domains containing amorphous resins. If the size of the domains made of amorphous resins is small, the amorphous resin can enter the gaps between the fibers of the paper during low-temperature fixing and adhere to the paper. On the other hand, if the size of the domains made of amorphous resins is large, the amorphous resin can increase the surface area and adhere to the fibers of the paper. Therefore, the eraser abrasion resistance can be improved by having a certain ratio of relatively small domains and large domains, and by having the domains widely dispersed in the toner. Therefore, (a) and (b) are satisfied.

[0020] The toner will be described in detail below. When a cross section of the toner is observed with a scanning transmission electron microscope, a domain matrix structure in which domains are dispersed in a matrix is ​​observed on the cross section. The matrix contains a crystalline resin A, and the domains contain an amorphous resin B. When a domain having a major axis of 300 nm or more is called a domain C, and a domain having a major axis of 200 nm or less is called a domain D, the number-average major axis of domain D is 30 to 150 nm.

[0021] By including the crystalline resin A in the matrix, excellent low-temperature fixability can be obtained. By having the number-average major axis of the domains D be 30 to 150 nm, the toner has excellent high gloss over a wide temperature range. If the number-average major axis of the domains D is smaller than 30 nm, the domains will penetrate too much into the gaps in the paper during fixing at higher temperatures, causing the effects of unevenness on the paper and reducing gloss. On the other hand, if the number-average major axis of the domains D is larger than 150 nm, the domains D will not melt sufficiently during low-temperature fixing, causing unevenness of the toner on the paper surface and reducing gloss. The number-average major axis of the domains D is preferably 40 to 120 nm, more preferably 50 to 100 nm.

[0022] The number-average major axis of domains D can be controlled by the ratio of crystalline components in crystalline resin A, the ratio of components having high affinity with crystalline resin A in amorphous resin B, and the ratio of crystalline resin A to amorphous resin B. Specifically, the number-average major axis of domains D can be increased by increasing the ratio of crystalline components in crystalline resin A, decreasing the ratio of components having high affinity with crystalline resin A in amorphous resin B, and decreasing the ratio of crystalline resin A. In addition, the number-average major axis of domains D can be decreased by decreasing the ratio of crystalline components in crystalline resin A, increasing the ratio of components having high affinity with crystalline resin A in amorphous resin B, and increasing the ratio of crystalline resin A.

[0023] In the present disclosure, (b) the ratio of toner cross sections that satisfy both of the following (i) and (ii) is 90% or more by number. (i) There are 5 to 20 domains C per cross section of one toner particle, and the area ratio of the domains C is 10 to 30 area % based on the cross section area. (ii) In the cross section of the toner, domain D is observed over the entire area except for domain C.

[0024] When the cross-sectional area ratio of domains C and D satisfying both (i) and (ii) is 90% or more, the toner has excellent eraser abrasion resistance during low-temperature fixing. When the number and area ratio of domains C are small, the domains that can adhere to the paper fibers over a large area are reduced, and the eraser abrasion resistance is reduced. On the other hand, when the number and area ratio of domains C are large, unevenness of the toner occurs on the paper surface during low-temperature fixing, and the gloss is reduced. do.

[0025] Furthermore, if domain D does not exist over the entire surface except for domain C, that is, if domain D exists unevenly, domain D will get into the gaps in the paper and some parts will not be able to adhere, resulting in poor eraser abrasion resistance. Therefore, if the proportion of cross sections of the toner that satisfy both (i) and (ii) is less than 90%, eraser abrasion resistance will be poor. The proportion of cross sections that satisfy both (i) and (ii) is preferably 95 to 100% by number, more preferably 97 to 100% by number.

[0026] In addition, the proportion of cross sections in which the area ratio of domain C is 15 to 25 area % based on the cross section area is preferably 90% by number or more, more preferably 90 to 100% by number, and even more preferably 92 to 100% by number, among the cross sections of the toner. When it is in this range, the eraser abrasion resistance is more likely to be improved.

[0027] Among domains C, domains with a major axis of 400 nm or more are referred to as domains E. It is preferable that the ratio of the cross sections of the toner particles in which 4 to 20 domains E exist per cross section of one toner particle is 90% or more by number. By being in this range, the eraser abrasion resistance is further improved. The ratio of the cross sections is preferably 92 to 100% by number, and more preferably 94 to 100% by number. In order to set the proportion of the cross section within the above range, it is easy to control it by the proportion of the crystalline component in crystalline resin A, the proportion of the component having high affinity with crystalline resin A in amorphous resin B, and further the ratio of crystalline resin A to amorphous resin B. Specifically, the proportion of the cross section can be easily set within the above range by increasing the proportion of the crystalline component in crystalline resin A, decreasing the proportion of the component having high affinity with crystalline resin A in amorphous resin B, and decreasing the proportion of crystalline resin A.

[0028] It is also preferable that 100 or more domains D are present in any 1 μm square area excluding domains C. This state means that domains D are present relatively uniformly in the toner particles, which makes it easier to improve eraser abrasion resistance.

[0029] In order to satisfy the above (i) and "the proportion of the cross section in which the area ratio of domain C is 15 to 25 area % based on the cross section area", there is a means for controlling the number and area of ​​domain C. The number and area of ​​domain C can be controlled by the compatibility between amorphous resin B and crystalline resin A. If amorphous resin B is made compatible with crystalline resin A, the number of domains C tends to be small and the area also tends to be small. To achieve this, for example, there is a method of using a material having a common structural unit that reduces the SP value difference between crystalline resin A and amorphous resin B. On the other hand, if the amorphous resin B is made less compatible with the crystalline resin A, the number and area of ​​domains C can be increased. To achieve this, for example, there is a method of increasing the difference in SP value between the crystalline resin A and the amorphous resin B, or of using materials having common structural units as little as possible.

[0030] The toner particles contain crystalline resin A and amorphous resin B. The toner particles contain, for example, as binder resins, crystalline resin A and amorphous resin B. The crystalline resin A will be described. Examples of the crystalline resin A include vinyl resins, polyester resins, polyurethane resins, and epoxy resins having crystallinity, and vinyl resins having crystallinity are preferred.

[0031] When the crystalline resin A is a vinyl resin having crystallinity, it preferably has a monomer unit represented by the following formula (1) (hereinafter also referred to as monomer unit (a)). In formula (1), R 4 represents a hydrogen atom or a methyl group, and n represents an integer of 15 to 35. [ka]

[0032] Formula (1) indicates that the vinyl resin has a long-chain alkyl group, and the vinyl resin tends to exhibit crystallinity when n in formula (1) is 15 to 35. n is preferably 17 to 29.

[0033] As a method for introducing the monomer unit (a), there is a method of polymerizing the following (meth)acrylic acid esters. For example, (meth)acrylic acid esters having a linear alkyl group having 16 to 36 carbon atoms [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosanyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, octacosyl (meth)acrylate, myricyl (meth)acrylate, dotriacontyl (meth)acrylate, etc.] and (meth)acrylic acid esters having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.] can be mentioned.

[0034] The monomer unit represented by formula (1) may be used alone or in combination of two or more kinds. When the crystalline resin A is a vinyl resin having crystallinity, it is possible to have other monomer units in addition to the monomer unit (a). As a method for introducing other monomer units, there is a method of polymerizing the (meth)acrylic acid ester and other vinyl monomers. The other monomer units may be used alone or in combination of two or more kinds.

[0035] Other vinyl monomers include the following: (Meth)acrylic acid esters such as styrene, α-methylstyrene, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Monomer having a urea group: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amine (such as normal butylamine, t-butylamine, propylamine, and isopropylamine), secondary amine (such as di-normal ethylamine, di-normal propylamine, and di-normal butylamine), aniline, and cycloxylamine] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method. Monomers having a carboxy group; for example, methacrylic acid, acrylic acid, 2-carboxyethyl (meth)acrylate, etc. Monomers having a hydroxy group; for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, etc. Monomers having an amide group; for example, acrylamide, monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms (such as acrylic acid and methacrylic acid) having an ethylenically unsaturated bond by a known method, and the like. Monomers having a lactam structure; for example, N-vinyl-2-pyrrolidone.

[0036] Among them, it is preferable that the crystalline resin A contains a monomer unit having a lactam structure, and it is more preferable that the crystalline resin A contains a monomer unit having a five-membered ring lactam structure. It is preferable to use N-vinyl-2-pyrrolidone as a monomer having a five-membered ring lactam structure. When the crystalline resin A has a lactam structure, the affinity between the crystalline resin A and paper is improved, and it is easier to further improve the eraser abrasion resistance.

[0037] The monomer unit having a lactam structure may be represented by the following formula (L) (preferably formula (L-1)): The crystalline resin A preferably contains the monomer unit represented by formula (L) (preferably formula (L-1)) in an amount of 1.0 to 15.0 mass %, more preferably 4.0 to 12.0 mass %. [ka] In formulae (L) and (L-1), R2 represents a hydrogen atom or a methyl group, and n is an integer of 1 to 4 (preferably 1 to 3).

[0038] When the crystalline resin A is a vinyl resin having crystallinity, the content of the monomer unit (a) in the crystalline vinyl resin is preferably 45.0 to 90.0 mass%, more preferably 50.0 to 80.0 mass%, and even more preferably 60.0 to 70.0 mass%. When the content of the monomer unit (a) is within the above range, the size and number of the domains C and D can be easily controlled.

[0039] The crystalline resin A may contain a monomer unit based on styrene. The crystalline resin A preferably contains 3.0 to 25.0% by mass, and more preferably 10.0 to 20.0% by mass, of the monomer unit based on styrene. The crystalline resin A may contain at least one monomer unit selected from the group consisting of acrylonitrile and methacrylonitrile. The crystalline resin A preferably contains 5.0 to 25.0 mass % of the at least one monomer unit selected from the group consisting of acrylonitrile and methacrylonitrile, and more preferably contains 8.0 to 17.0 mass %.

[0040] The crystalline resin A may be a polyester resin. The polyester resin may be a condensation polymer of a divalent or higher polyvalent carboxylic acid and a polyhydric alcohol.

[0041] Examples of polycarboxylic acids include the following compounds: Examples of the dibasic acids include succinic acid, adipic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, malonic acid, and dodecenylsuccinic acid, and their anhydrides or lower alkyl esters, as well as aliphatic unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and citraconic acid. Other examples include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, and anhydrides or lower alkyl esters thereof. These may be used alone or in combination of two or more.

[0042] Examples of the polyhydric alcohol include the following compounds: Examples of the alkylene glycol include alkylene glycols (ethylene glycol, 1,2-propylene glycol, and 1,3-propylene glycol); alkylene ether glycols (polyethylene glycol and polypropylene glycol); alicyclic diols (1,4-cyclohexanedimethanol); bisphenols (bisphenol A); and alkylene oxide (ethylene oxide and propylene oxide) adducts of alicyclic diols. The alkyl moieties of the alkylene glycols and alkylene ether glycols may be linear or branched. Further examples include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, etc. These may be used alone or in combination of two or more.

[0043] For the purpose of adjusting the acid value or hydroxyl value, monovalent acids such as acetic acid and benzoic acid, and monovalent alcohols such as cyclohexanol and benzyl alcohol can also be used as necessary. The method for producing the polyester resin is not particularly limited, and for example, a transesterification method or a direct polycondensation method can be used alone or in combination.

[0044] The weight average molecular weight Mw of the crystalline resin A is preferably 15,000 to 50,000, and more preferably 20,000 to 40,000. The ratio Mw / Mn of the weight average molecular weight Mw of the crystalline resin A to the number average molecular weight Mn is preferably 2.0 to 6.5, and more preferably 2.5 to 5.5.

[0045] The content of the crystalline resin A in the binder resin is preferably 10.0% by mass or more and 70.0% by mass or less. Within the above range, a domain matrix structure is easily obtained, and the size and number of the domains C and D are easily controlled. The content of the crystalline resin A in the binder resin is more preferably 15.0 to 60.0% by mass, further preferably 20.0 to 50.0% by mass, further more preferably 30.0 to 40.0% by mass, and particularly preferably 33.0 to 37.0% by mass.

[0046] Next, a description will be given of the amorphous resin B. Examples of the amorphous resin B include vinyl resin, polyester resin, polyurethane resin, and epoxy resin. The amorphous resin B is preferably a vinyl resin or a polyester resin, and more preferably a vinyl resin.

[0047] When the amorphous resin B is a vinyl resin, the amorphous resin B preferably has a monomer unit (d) represented by the following formula (2): 5represents a hydrogen atom or a methyl group, and m represents an integer of 3 to 35. [ka]

[0048] When the amorphous resin B has the monomer unit (d), it becomes easier to control the compatibility between the amorphous resin B and the crystalline resin A, it becomes easier to form a domain matrix structure, and it becomes easier to control the size and number of the domains C and D. The preferred range of m is 3 or more and 29 or less, more preferably 3 or more and 19 or less, even more preferably 3 or more and 15 or less, and even more preferably 3 or more and 5 or less.

[0049] As a method for introducing the monomer unit (d), in addition to the (meth)acrylic acid esters usable in the above-mentioned monomer unit (a), there is a method of polymerizing the following (meth)acrylic acid esters: For example, n-butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, etc. can be mentioned.

[0050] The monomer unit (d) may be used alone or in combination of two or more kinds. When the amorphous resin B is a vinyl resin, it may have other monomer units in addition to the monomer unit (d). As a method for introducing other monomer units, there is a method of polymerizing the (meth)acrylic acid ester and the vinyl monomer usable for the crystalline resin A described above.

[0051] When the amorphous resin B is a vinyl resin, the proportion of the monomer unit (d) is preferably 5.0% by mass or more and 40.0% by mass or less. The lower limit is more preferably 10.0% by mass or more, even more preferably 13.0% by mass or more, and even more preferably 15.0% by mass or more. The upper limit is more preferably 35.0% by mass or less, even more preferably 30.0% by mass or less, and even more preferably 20.0% by mass or less. Furthermore, the amorphous resin B may contain a monomer unit based on styrene. The amorphous resin B preferably contains 50.0 to 95.0 mass % of the monomer unit based on styrene, and more preferably contains 60.0 to 80.0 mass %.

[0052] When the amorphous resin B is a polyester resin, among the polyester resins obtainable by the reaction of the above-mentioned divalent or higher polyvalent carboxylic acid and polyhydric alcohol, a resin that does not exhibit crystallinity can be used.

[0053] The toner preferably has a weight average molecular weight (Mw) of tetrahydrofuran (THF) soluble matter measured by gel permeation chromatography (GPC) of 10,000 or more and 200,000 or less. The lower limit is more preferably 30,000 or more, and even more preferably 50,000 or more. The upper limit is more preferably 180,000 or less. When Mw is within the above range, the durability of the toner is easily improved. The ratio (Mw / Mn) of the weight average molecular weight (Mw) of the THF soluble portion of the toner to the number average molecular weight (Mn) is preferably from 5.0 to 15.0, and more preferably from 7.0 to 12.0.

[0054] The toner has a weight average particle diameter of 4.0 to 10.0 μm. With the weight average particle diameter in the above range, it is possible to achieve both low-temperature fixability and high gloss over a wide temperature range. The weight average particle diameter of the toner is preferably 5.0 μm or more and 9.0 μm or less, and more preferably 5.3 μm or more and 8.5 μm or less.

[0055] The melting point of the toner derived from the crystalline resin A measured by a differential scanning calorimeter (DSC) is preferably 50° C. or more and 80° C. or less. When the melting point derived from the crystalline resin A is in the above range, low-temperature fixability can be further improved. The preferred range of the melting point is 55° C. or more and 75° C. or less, more preferably 57° C. or more and 70° C. or less.

[0056] The toner may contain a release agent. The release agent is at least one selected from the group consisting of a hydrocarbon wax and an ester wax. By using a hydrocarbon wax and / or an ester wax, effective releasability can be easily ensured. The release agent preferably contains an ester wax, and more preferably contains a polyfunctional ester wax. The polyfunctional ester wax improves abrasion resistance and gloss at high temperatures.

[0057] The polyfunctional ester wax refers to an ester compound of a polyhydric alcohol and a monocarboxylic acid, and an ester compound of a polycarboxylic acid and a monoalcohol. The polyfunctional ester wax is preferably at least one ester compound selected from the group consisting of an ester compound of a tetravalent to octavalent alcohol and an aliphatic monocarboxylic acid, and an ester compound of a tetravalent to octavalent carboxylic acid and an aliphatic monoalcohol. More preferably, the polyfunctional ester wax is at least one ester compound selected from the group consisting of an ester compound of a hexavalent to octavalent alcohol and an aliphatic monocarboxylic acid, and an ester compound of a hexavalent to octavalent carboxylic acid and an aliphatic monoalcohol.

[0058] The hydrocarbon wax is not particularly limited, but examples thereof include the following: Aliphatic hydrocarbon waxes: low molecular weight polyethylene, low molecular weight polypropylene, low molecular weight olefin copolymer, Fischer-Tropsch wax, or waxes obtained by oxidizing or adding an acid to these.

[0059] The ester wax may be any wax having at least one ester bond in one molecule, and may be either a natural ester wax or a synthetic ester wax. The ester wax is not particularly limited, but examples thereof include the following. Esters of monohydric alcohols and monocarboxylic acids, such as behenyl behenate, stearyl stearate, and palmityl palmitate; Esters of divalent carboxylic acids and monoalcohols, such as dibehenyl sebacate; Esters of dihydric alcohols and monocarboxylic acids, such as ethylene glycol distearate and hexanediol dibehenate; Esters of trihydric alcohols and monocarboxylic acids, such as glycerin tribehenate; Esters of tetrahydric alcohols and monocarboxylic acids, such as pentaerythritol tetrastearate and pentaerythritol tetrapalmitate; Esters of hexahydric alcohols and monocarboxylic acids, such as dipentaerythritol hexastearate, dipentaerythritol hexapalmitate, and dipentaerythritol hexabehenate; Esters of polyfunctional alcohols and monocarboxylic acids, such as polyglycerin behenate; natural ester waxes, such as carnauba wax and rice wax

[0060] Among these, at least one selected from the group consisting of esters of hexahydric alcohols and monocarboxylic acids, such as dipentaerythritol hexastearate, dipentaerythritol hexapalmitate, and dipentaerythritol hexabehenate, and esters of octahydric alcohols and monocarboxylic acids, such as tripentaerythritol octastearate, tripentaerythritol octapalmitate, and tripentaerythritol octabehenate, is preferred. As the release agent, a hydrocarbon wax or an ester wax may be used alone, or a hydrocarbon wax and an ester wax may be used in combination, or two or more of each may be mixed and used.

[0061] In the toner, the content of the release agent in the toner particles is preferably 1.0 to 30.0% by mass, more preferably 2.0 to 25.0% by mass, further preferably 5.0 to 15.0% by mass, and even more preferably 6.0 to 13.0% by mass. When the content of the release agent in the toner particles is within the above range, the effects of abrasion resistance and high gloss at high temperatures can be easily obtained.

[0062] The melting point of the release agent is preferably 60 to 120° C. When the melting point of the release agent is in the above range, the release agent melts during fixing and easily seeps out onto the toner particle surface, and the release property is easily exhibited. The melting point of the release agent is more preferably 70 to 100° C.

[0063] The toner may contain a colorant. Examples of the colorant include known organic pigments, organic dyes, inorganic pigments, carbon black as a black colorant, magnetic particles, etc. In addition, colorants that have been used in conventional toners may also be used. Examples of yellow colorants include condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specifically, CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 109, 110, 111, 128, 129, 147, 155, 168, and 180 are preferably used.

[0064] Examples of magenta colorants include condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specifically, CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221, and 254 are preferably used. Examples of cyan colorants include copper phthalocyanine compounds and their derivatives, anthraquinone compounds, and basic dye lake compounds. Specifically, CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66 are preferably used.

[0065] The colorant is selected in consideration of hue angle, chroma, brightness, light resistance, transparency on an OHP sheet, and dispersibility in the toner. The content of the colorant is preferably 1.0 to 20.0 parts by mass with respect to 100.0 parts by mass of the binder resin. When magnetic particles are used as the colorant, the content is preferably 40.0 to 150.0 parts by mass with respect to 100.0 parts by mass of the binder resin.

[0066] If necessary, a charge control agent may be contained in the toner particles. Alternatively, the charge control agent may be added externally to the toner particles. By blending the charge control agent, it becomes possible to stabilize the charge characteristics and control the amount of triboelectric charge optimally according to the development system. As the charge control agent, known ones can be used. In particular, those having a high charging speed and a constant charging speed can be used. A charge control agent capable of stably maintaining the charge amount is preferred.

[0067] As the charge control agent that controls the toner to have a negative charge, the following can be mentioned. Organometallic compounds and chelate compounds are effective, and examples thereof include monoazo metal compounds, acetylacetone metal compounds, aromatic oxycarboxylic acids, aromatic dicarboxylic acids, oxycarboxylic acids and dicarboxylic acid-based metal compounds. The following can be mentioned as the substances that control the toner to have a positive charge. Examples of the organic solvent include nigrosine, quaternary ammonium salts, metal salts of higher fatty acids, diorgano tin borates, guanidine compounds, and imidazole compounds. The content of the charge control agent is preferably 0.01 to 20.0 parts by mass, and more preferably 0.5 to 10.0 parts by mass, relative to 100.0 parts by mass of the toner particles.

[0068] The toner particles may be used as they are as a toner, or may be mixed with an external additive, if necessary, and attached to the surface of the toner particles to form a toner. The external additive may be an inorganic fine particle selected from the group consisting of silica fine particles, alumina fine particles, and titania fine particles, or a composite oxide thereof, etc. Examples of the composite oxide include silica aluminum fine particles and strontium titanate fine particles. The content of the external additive is preferably 0.01 to 8.0 parts by mass, and more preferably 0.1 to 4.0 parts by mass, relative to 100 parts by mass of the toner particles.

[0069] The toner particles may be produced by any known method, such as a suspension polymerization method, an emulsion aggregation method, a dissolution suspension method, or a pulverization method, so long as it falls within the scope of the present invention, but it is preferable to produce the toner particles by a suspension polymerization method.

[0070] The suspension polymerization method will now be described in detail. For example, a previously synthesized crystalline resin A is mixed with each polymerizable monomer for producing an amorphous resin B. If necessary, other materials such as a colorant, a release agent, and a charge control agent are also mixed and uniformly dissolved or dispersed to prepare a polymerizable monomer composition.

[0071] Thereafter, the polymerizable monomer composition is dispersed in an aqueous medium using a stirrer or the like to prepare suspended particles of the polymerizable monomer composition, and then the polymerizable monomer contained in the particles is polymerized with an initiator or the like to obtain toner particles. After the polymerization is completed, the toner particles are filtered, washed and dried by known methods, and external additives are added as necessary to obtain the toner.

[0072] As the polymerization initiator, a known polymerization initiator can be used. Examples of the polymerization initiator include azo or diazo polymerization initiators such as 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile; and peroxide polymerization initiators such as benzoyl peroxide, t-butyl peroxy 2-ethylhexanoate, t-butyl peroxypivalate, t-butyl peroxyisobutyrate, t-butyl peroxyneodecanoate, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide. Furthermore, known chain transfer agents and polymerization inhibitors may be used.

[0073] The aqueous medium may contain an inorganic or organic dispersion stabilizer. As the dispersion stabilizer, known dispersion stabilizers can be used. Examples of inorganic dispersion stabilizers include phosphates such as hydroxyapatite, tricalcium phosphate, dicalcium phosphate, magnesium phosphate, aluminum phosphate, and zinc phosphate; carbonates such as calcium carbonate and magnesium carbonate; metal hydroxides such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide; sulfates such as calcium sulfate and barium sulfate; calcium metasilicate; bentonite; silica; and alumina.

[0074] On the other hand, examples of organic dispersion stabilizers include polyvinyl alcohol, gelatin, methyl cellulose, methylhydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, polyacrylic acid and its salts, and starch.

[0075] When an inorganic compound is used as the dispersion stabilizer, a commercially available product may be used as it is, but in order to obtain finer particles, the inorganic compound may be formed in an aqueous medium and then used. For example, in the case of calcium phosphates such as hydroxyapatite or tricalcium phosphate, an aqueous solution of the phosphate may be mixed with an aqueous solution of the calcium salt under high agitation.

[0076] The aqueous medium may contain a surfactant. As the surfactant, a known surfactant can be used. For example, anionic surfactants such as sodium dodecylbenzene sulfate and sodium oleate, cationic surfactants, amphoteric surfactants, nonionic surfactants, etc. can be mentioned.

[0077] The calculation and measurement methods for various physical properties of the toner and toner materials are described below. <Method of observing toner cross section using a transmission electron microscope (TEM) and measuring the major axis and number of domains> The domain matrix structure is observed after staining the toner cross section with ruthenium. First, the toner is spread on a cover glass (Matsunami Glass Co., Ltd., square cover glass No. 1) so that it becomes a single layer. Then, using an osmium plasma coater (Filgen Co., Ltd., OPC80T), an Os film (5 nm) and a naphthalene film (20 nm) are applied to the toner as a protective film. Next, a PTFE tube (inner diameter Φ1.5 mm × outer diameter Φ3 mm × 3 mm) is filled with photocurable resin D800 (JEOL Ltd.), and the above cover glass is gently placed on top of the tube so that the toner is in contact with the photocurable resin D800. In this state, light is irradiated to harden the resin, and then the cover glass and tube are removed to form a cylindrical resin with toner embedded in the outermost surface. Using an ultrasonic ultramicrotome (Leica, UC7), a cutting speed of 0.6 mm / s was used to cut the length of the toner radius (4.0 μm when the weight average particle size (D4) is 8.0 μm) from the outermost surface of the cylindrical resin to expose the cross section of the toner. Next, cutting was performed to a film thickness of 250 nm to prepare a thin sample of the toner cross section. By cutting in this manner, a cross section of the center of the toner can be obtained.

[0078] The obtained thin section sample was stained for 15 minutes in a RuO4 gas atmosphere of 500 Pa using a vacuum electron staining device (filgen, VSC4R1H) and observed using a STEM (JEOL, JEM2800). The probe size in the STEM observation was 1 nm, and the image size was 1024 × 1024 pixels. The obtained bright-field images were binarized using the image processing software "Image-ProPlus (Media Cybernetics)". The binarization process was carried out at 127 gradations or less when the change in luminance from black to white is taken as 0 gradations to 255 gradations. This process colors the parts with 128 or more tones black and the parts with 128 or more tones white. In observing a cross section of the toner, the parts containing crystalline resin A are the parts that appear black when the above-mentioned binarization process is performed, and the parts containing amorphous resin B are the parts that appear white when the above-mentioned binarization process is performed.

[0079] From the image obtained by STEM observation after the binarization process, it was judged whether a domain matrix structure was observed in the cross section of the toner. It was also judged whether the domain and matrix contained crystalline resin A or amorphous resin B, respectively. If the ratio of the cross sections of particles forming a domain matrix structure among the cross sections of the toner is 80% by number or more, it is judged that the cross section of the toner to be measured has a domain matrix structure. The domain matrix structure is a state in which domains, which are discontinuous phases, are dispersed in a matrix, which is a continuous phase.

[0080] Next, toner particles to be observed for measuring the major axis of the domain are selected as follows. First, the cross-sectional area of ​​the toner particle is calculated from the cross-sectional image of the toner particle, and the diameter of a circle having an area equal to that cross-sectional area (equivalent circle diameter) is calculated. Toner particles for which the absolute value of the difference between this equivalent circle diameter and the weight average particle diameter (D4) of the toner particles is 1.0 μm or less are selected as the observation object. Then, 100 toner particles to be observed are selected. Next, the major axis of the domain (white area when the domain is amorphous resin B) observed in the cross section of the toner particle selected for observation is measured. Among them, the domain with a major axis of 300 nm or more is called domain C, and the domain with a major axis of 200 nm or less is called domain D. The number average major axis of domain D of 100 toner particles is calculated.

[0081] In addition, the ratio of the cross sections which satisfy both (i) and (ii) is calculated. (i) There are 5 to 20 domains C per cross section of one toner particle, and the area ratio of the domains C is 10 to 30 area % based on the area of ​​the cross section. (ii) In the cross section, domain D is observed over the entire area except domain C. Here, whether or not domain D is observed over the entire surface is judged as follows: Three 1 μm square regions excluding domain C on the cross section of the toner particle are selected. If the number of domain D in each of the three 1 μm square regions is 30 or more, it is judged that "domain D is observed over the entire surface."

[0082] Also, the ratio of cross sections where the area ratio of domain C is 15 to 25 area % based on the cross section area of ​​the toner is calculated. Furthermore, among domain C, domains with a major axis of 400 nm or more are designated as domain E. Then, the ratio of cross sections where 4 to 20 domains E exist per toner particle is calculated. In addition, an arbitrary 1 μm square region excluding domain C in the cross section of the toner particle is selected, and the number of domains D in the 1 μm square region is calculated. The arithmetic average value of 100 particles to be observed is adopted.

[0083] (Ruthenium dyeing principle) When the cross section of a toner particle is stained with ruthenium, the crystalline resin component is stained with ruthenium more than the amorphous resin component, resulting in a clearer contrast and making it easier to observe the cross section of the toner particle. This is because RuO4 has a strong oxidizing power and oxidizes the long-chain alkyl and alkylene that increase crystallinity, resulting in the crystalline resin component being stained more strongly than the amorphous resin component.

[0084] In addition, the higher the crystallinity of the resin component, the greater the amount of ruthenium atoms present, and the greater the amount of ruthenium atoms present, the less electron beams can pass through. In the image observed under a microscope, the crystalline resin component is observed to be more strongly stained. In contrast, the amorphous resin component is observed to be weakly stained or not stained at all. From this, it can be determined that the strongly stained portion is the portion containing the crystalline resin, and the weakly stained portion or the portion not stained is the portion containing the amorphous resin.

[0085] <Method of measuring weight average particle size (D4) of toner> The weight-average particle size (D4) of the toner is calculated as follows. The measurement device used is a precision particle size distribution measurement device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube. The measurement conditions are set and the measurement data is analyzed using the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.). The measurement is performed with an effective measurement channel count of 25,000 channels. The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.). Before carrying out the measurement and analysis, the dedicated software was set up as follows.

[0086] In the "Change standard measurement method (SOMME)" screen of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard particle 10.0 μm" (Beckman Coulter). Press the "Threshold / Noise level measurement button" to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check "Flush aperture tube after measurement." In the "Pulse to particle size conversion setting" screen of the dedicated software, the bin interval is set to logarithmic particle size, the particle size bin is set to 256 particle size bins, and the particle size range is set to 2 μm to 60 μm.

[0087] The specific measurement method is as follows. (1) Pour about 200 ml of the electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, remove dirt and air bubbles from inside the aperture tube using the "Aperture Tube Flush" function of the dedicated software. (2) 30 ml of the electrolyte solution is placed in a 100 ml flat-bottom glass beaker, and 0.3 ml of a dilution of "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments made of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion-exchanged water is added as a dispersant. (3) Prepare an ultrasonic disperser "Ultrasonic Dispension System Tetra150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees, and has an electrical output of 120 W. Place 3.3 L of ion-exchanged water in the ultrasonic disperser's water tank, and add 2 ml of Conaminon N to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, 10 mg of toner is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, the electrolytic solution (5) in which the toner is dispersed is dropped into the round-bottom beaker (1) placed in the sample stand, and the measurement concentration is adjusted to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen is the weight-average particle size (D4).

[0088] <Measuring method of melting point of crystalline resin A in differential scanning calorimetry (DSC) measurement of toner> The melting point of the toner is measured using a DSC Q2000 (manufactured by TA Instruments) under the following conditions. Heating rate: 10℃ / min Measurement start temperature: 20℃ End of measurement temperature: 180℃ The melting points of indium and zinc are used for temperature correction of the device detection section, and the heat of fusion of indium is used for heat correction. Specifically, 5 mg of sample is weighed out and placed in an aluminum pan, and differential scanning calorimetry is performed. An empty silver pan is used as a reference. The temperature is raised to 180°C at a rate of 10°C / min. The peak temperature is calculated from each peak.

[0089] When the maximum endothermic peak, that is, the endothermic peak thought to be derived from the crystalline resin A, does not overlap with other endothermic peaks such as those of the release agent, the temperature at the maximum endothermic peak is regarded as the melting point of the toner. On the other hand, when the endothermic peak of another agent such as a release agent overlaps with the maximum endothermic peak, it is necessary to subtract the endothermic peak originating from the release agent, etc. For example, the endothermic peak due to the crystalline resin A can be obtained by subtracting the endothermic amount due to the release agent by the following method.

[0090] First, the release agent is subjected to a separate DSC measurement to determine its endothermic properties. Next, the release agent content in the toner is determined. The release agent content in the toner can be measured by a known structural analysis. Then, the amount of endothermic heat caused by the release agent is calculated from the release agent content in the toner, and this amount is subtracted from the peak caused by the binder resin. In the case where the release agent is easily compatible with the binder resin component, it is necessary to multiply the content of the release agent by the compatibility rate, and then calculate and subtract the amount of heat absorption caused by the release agent. The compatibility rate is calculated by dividing the amount of heat absorption determined for a molten mixture of the resin components and the release agent in the same ratio as the content rate of the release agent by the theoretical amount of heat absorption calculated from the amount of heat absorption of the molten mixture determined in advance and the amount of heat absorption of the release agent alone.

[0091] <Method of measuring the molecular weight of toner> The molecular weight (weight average molecular weight Mw) of the THF-soluble portion of the toner is measured by gel permeation chromatography (GPC) as follows. First, the toner is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The resulting solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of components soluble in THF is 0.8 mass %. This sample solution is used to perform measurements under the following conditions. Equipment: HLC8120 GPC (detector: RI) (Tosoh Corporation) Column: 7 columns of Shodex KF-801, 802, 803, 804, 805, 806, 807 (Showa Denko Co., Ltd.) Eluent: Tetrahydrofuran (THF) ·Flow rate: 1.0ml / min Oven temperature: 40.0℃ Sample injection volume: 0.10ml When calculating the molecular weight of the sample, a standard polystyrene resin (for example, TSK A molecular weight calibration curve prepared using standard polystyrene (F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500, manufactured by Tosoh Corporation) is used.

[0092] <Method of separating crystalline resin A and amorphous resin B from toner> The crystalline resin A and the amorphous resin B can be separated from the toner by a known method, and an example will be described below. Gradient polymer LC is used as a method for separating resin components from toner. This analysis allows separation according to the polarity of the resin in the binder resin, regardless of the molecular weight.

[0093] First, the toner is dissolved in chloroform. The sample concentration is adjusted to 0.1% by mass in chloroform, and the solution is filtered through a 0.45 μm PTFE filter before being used for measurement. The gradient polymer LC measurement conditions are as follows. Equipment: UlTIMATE3000 (Thermo Fisher Scientific) Mobile phase: A Chloroform (HPLC), B Acetonitrile (HPLC) Gradient: 2min (A / B=0 / 100) → 25min (A / B=100 / 0) (Note that the gradient of the change in the mobile phase was made linear.) Flow rate: 1.0mL / min Injection: 0.1% by mass x 20μL Column: Tosoh TSKgel ODS (4.6mmφx150mm x 5μm) Column temperature: 40℃ Detector: Corona Charged Aerosol Detector (Corona-CAD) (Thermo Fisher Scientific)

[0094] The time-intensity graph obtained from the measurement shows that the resin components can be separated into two peaks depending on the polarity. After that, the above measurement is carried out again, and by taking fractions at the time when each peak reaches its valley, it is possible to separate the two types of resin. The separated resins are subjected to DSC measurement. Resins that have a melting point peak are designated as crystalline resin A, and those that do not have a melting point peak are designated as amorphous resin B.

[0095] When the toner contains a release agent, the release agent is separated by recycling HPLC to separate components with a molecular weight of 3000 or less as the release agent. The measurement method is as follows. First, a chloroform solution of the toner is prepared by the method described above. The obtained solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of components soluble in chloroform is 1.0 mass %. This sample solution is used to perform measurements under the following conditions. ·Equipment: LC-Sakura NEXT (manufactured by Nippon Analytical Industry Co., Ltd.) Column: JAIGEL 2H, 4H (Japan Analytical Industry Co., Ltd.) Eluent: Chloroform ·Flow rate: 10.0ml / min Oven temperature: 40.0℃ Sample injection volume: 1.0ml In calculating the molecular weight of the sample, standard polystyrene resins (e.g., trade names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-25 A molecular weight calibration curve prepared using "A-00, A-1000, A-500" (manufactured by Tosoh Corporation) is used. From the molecular weight curve thus obtained, components having a molecular weight of 3000 or less are repeatedly separated to remove the release agent from the toner. Note that the molecular weight to be separated can be changed in consideration of the molecular weight of the release agent.

[0096] <Method of measuring the content of various monomer units such as monomer unit (a) in a resin and the number of carbon atoms in the alkyl group> The content ratio of various monomer units (a) in the resin and the number of carbon atoms in the alkyl group are measured by 1 The measurement is performed by H-NMR under the following conditions. The crystalline resin A separated by the above-mentioned method can be used as the measurement sample. Measuring device: FT NMR device JNM-EX400 (manufactured by JEOL Ltd.) Measurement frequency: 400MHz Pulse condition: 5.0μs Frequency range: 10500Hz Number of times: 64 Measurement temperature: 30℃ Sample: 50 mg of the measurement sample is placed in a sample tube with an inner diameter of 5 mm, deuterated chloroform (CDCl3) is added as a solvent, and this is dissolved in a constant temperature bath at 40°C to prepare the sample. Obtained 1 The H-NMR chart is analyzed to identify the structure of each monomer unit. As an example, the measurement of the content ratio of monomer unit (a) in crystalline resin A and the number of carbon atoms in the alkyl group is described below. Obtained 1 In the H-NMR chart, a peak that is independent of the peaks that are attributable to the components of the monomer unit (a) is selected from the peaks that are attributable to the components of the other monomer units, and the integral value S1 of this peak is calculated. The integral values ​​of the other monomer units contained in the crystalline resin A are also calculated in the same manner.

[0097] When the monomer units constituting the crystalline resin A are the monomer unit (a) and one other monomer unit, the content of the monomer unit (a) is determined as follows using the above integral value S1 and the integral value S2 of the peak of the other monomer unit, where n1 and n2 are the numbers of hydrogen atoms in the constituent elements to which the peak of interest for each site belongs. Content of monomer unit (a) (mol%)= {(S1 / n1) / ((S1 / n1)+(S2 / n2))}×100 Even when two or more types of other monomer units are present, the content of the monomer unit (a) can be calculated in the same manner (using S3···Sx, n3···nx). The number of carbon atoms in the alkyl group is 1 It can be calculated from the integral ratio of the proton peak in the H-NMR chart.

[0098] In addition, when a polymerizable monomer that does not contain a hydrogen atom in any component other than the vinyl group is used, 13 Measure nuclei using C-NMR 13 C, and the measurement was performed in single pulse mode. 1 The content of each monomer unit is converted to mass% by multiplying the proportion (mol%) of each monomer unit calculated by the above method by the molecular weight of each monomer unit. The content of each monomer unit is also measured using the same method for amorphous resin B. EXAMPLES

[0099] The present disclosure will be specifically described below with reference to examples, but these are not intended to limit the present disclosure in any way. In the following formulations, parts are by weight unless otherwise specified.

[0100] (Preparation of Crystalline Resin A1) The following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. Toluene 100.0 parts Monomer composition 100.0 parts (The monomer composition is a mixture of the following monomers in the ratio shown below.) (Behenyl acrylate 65.0 parts) (15.0 parts styrene) (Methacrylonitrile 10.0 parts) (N-vinyl-2-pyrrolidone 10.0 parts) Polymerization initiator: 0.5 parts t-butyl peroxypivalate (NOF Corp.: Perbutyl PV) The inside of the reaction vessel was heated to 70°C while stirring at 200 rpm, and polymerization reaction was carried out for 12 hours, to obtain a solution in which the polymer of the monomer composition was dissolved in toluene. Then, the temperature of the solution was lowered to 25°C, and the solution was poured into 1000.0 parts of methanol while stirring, to precipitate the methanol insoluble matter. The obtained methanol insoluble matter was filtered, washed with methanol, and then vacuum dried at 40°C for 24 hours to obtain crystalline resin A1. The physical properties of crystalline resin A1 are shown in Table 1.

[0101] (Preparation of Crystalline Resins A2 to A12) Crystalline Resins A2 to A12 were prepared in the same manner as in the preparation of Crystalline Resin A1, except that the amounts of the monomer composition and polymerization initiator added were changed to those shown in Table 1. Table 1 shows the physical properties of Crystalline Resins A2 to A12. [Table 1]

[0102] (Preparation of amorphous resin B1) 50.0 parts of xylene was charged into an autoclave, and after replacing with nitrogen, the temperature was raised to 185°C under agitation and in a sealed state. A mixed solution of 80.7 parts of styrene, 17.8 parts of n-butyl acrylate, 1.1 parts of divinylbenzene, and 0.5 parts of acrylic acid, as well as 1.5 parts of di-tert-butyl peroxide and 20.0 parts of xylene was added to the autoclave, and the temperature inside the autoclave was adjusted to 185°C. The mixture was continuously added dropwise for 3 hours while controlling the temperature at 185℃, and polymerization was continued. The mixture was kept for 1 hour to complete the polymerization, and the solvent was removed to obtain amorphous resin B1. The weight average molecular weight (Mw) of amorphous resin B1 was 40,000.

[0103] <Example 1> [Toner production by suspension polymerization method] (Production of toner particles 1) -16.2 parts n-butyl acrylate Styrene 48.8 parts Colorant Pigment Blue 15:3 6.5 parts The mixture was placed in an attritor (manufactured by Nippon Coke Corporation) and dispersed at 200 rpm for 2 hours using zirconia beads with a diameter of 5 mm to obtain a raw material dispersion.

[0104] On the other hand, 735.0 parts of ion-exchanged water and 16.0 parts of trisodium phosphate (12-hydrate) were added to a container equipped with a high-speed stirring device homomixer (manufactured by Primix Corporation) and a thermometer, and the temperature was raised to 60 ° C. while stirring at 12000 rpm. An aqueous calcium chloride solution in which 9.0 parts of calcium chloride (2-hydrate) was dissolved in 65.0 parts of ion-exchanged water was added thereto, and the mixture was stirred at 12000 rpm for 30 minutes while maintaining the temperature at 60 ° C. 10% hydrochloric acid was added thereto to adjust the pH to 6.0, and an aqueous medium in which an inorganic dispersion stabilizer containing hydroxyapatite was dispersed in water was obtained.

[0105] Next, the raw material dispersion liquid was transferred to a container equipped with a stirrer and a thermometer, and the temperature was raised to 60° C. while stirring at 100 rpm. ·Crystalline resin A1 35.0 parts Release agent 1 (DP18) 9.0 parts DP18 (dipentaerythritol stearate wax, melting point 79°C, manufactured by Nisshin Oillio Co., Ltd.) The above materials were added thereto and stirred at 100 rpm for 30 minutes while maintaining the temperature at 60°C, and then 5.0 parts of t-butyl peroxypivalate (Perbutyl PV, manufactured by NOF Corp.) was added as a polymerization initiator and stirred for another minute. Then, the mixture was poured into the aqueous medium being stirred at 12000 rpm by the high-speed stirring device. Stirring was continued for 20 minutes at 12000 rpm by the high-speed stirring device while maintaining the temperature at 60°C, to obtain a granulation liquid.

[0106] The granulation liquid was transferred to a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube, and heated to 70° C. while stirring at 150 rpm under a nitrogen atmosphere. A polymerization reaction was carried out at 150 rpm for 12 hours while maintaining the temperature at 70° C., to obtain a toner particle dispersion liquid. The resulting toner particle dispersion was cooled to 45°C while stirring at 150 rpm, and then heat-treated for 5 hours while maintaining the temperature at 45°C. Dilute hydrochloric acid was then added while maintaining the stirring until the pH reached 1.5 to dissolve the dispersion stabilizer. The solid content was filtered off, thoroughly washed with ion-exchanged water, and vacuum-dried at 30°C for 24 hours to obtain toner particles 1.

[0107] (Preparation of Toner 1) For the above toner particles, 1:98.0 parts, silica fine particles (hydrophobized with hexamethyldisilazane, number-average particle size of primary particles: 10 nm, BET specific surface area: 170 m) were added as an external additive. 2 2.0 parts of ethanol (1.0 parts / g) was added. The mixture was mixed at 3000 rpm for 15 minutes using a Henschel mixer (manufactured by Nippon Coke Corporation) to obtain toner 1. The physical properties of the obtained toner 1 are shown in Table 3, and the evaluation results are shown in Table 4.

[0108] [Table 2] Regarding the production method, SP indicates a suspension polymerization method, St indicates styrene, and the carbon number m indicates m in formula (2). Polymerization initiator: t-butyl peroxypivalate (NOF Corp.: Perbutyl PV) The tripentaerythritol stearate ester wax used was TP18 manufactured by Nisshin Oillio Co., Ltd. HNP51 is a paraffin wax manufactured by Nippon Seiro Co., Ltd.

[0109] [Table 3]

[0110] In the table, D4 ​​indicates the weight average particle size of the toner. Physical properties (1) to (4) are as follows. Physical property (1): The percentage (number%) of cross sections that satisfy both (i) and (ii) below (i) There are 5 to 20 domains C per cross section of one toner particle, and the area ratio of the domains C is 10 to 30% based on the cross-sectional area. (ii) In the cross section of a toner particle, in the region other than domain C, domain D is observed over the entire surface. Physical property (2): The ratio of the area of ​​domain C to the cross section of a toner particle, based on the cross section area, of 15 to 25% by area. (%) Physical property (3): The ratio (%) of cross sections of domains C that are 4 to 20 domains E with a major axis of 400 nm or more per toner particle Physical property (4): Whether there are 100 or more domains D in any 1 μm square area excluding domain C. In Examples 1 to 20 and Comparative Examples 1 to 4, regarding the physical property (1)(ii), domain D was observed over the entire surface.

[0111] <Examples 2 to 20> Toner particles 2 to 20 were obtained in the same manner as in Example 1, except that the type and amount of polymerizable monomer used, the amount of polymerization initiator added, and the type and amount of release agent added were changed as shown in Table 2. Furthermore, external addition was carried out in the same manner as in Example 1 to obtain toners 2 to 20. Table 3 shows the physical properties of the toners, and Table 4 shows the evaluation results.

[0112] <Comparative Examples 1 to 3 and 5> Comparative toner particles 1 to 3 and 5 were obtained in the same manner as in Example 1, except that the type and amount of polymerizable monomer used, the amount of polymerization initiator added, and the type and amount of release agent added were changed as shown in Table 2. Furthermore, external addition was carried out in the same manner as in Example 1 to obtain comparative toners 1 to 3 and 5. The physical properties of the toners are shown in Table 3, and the evaluation results are shown in Table 4. In Comparative Example 5, domains with major diameters exceeding 250 nm were observed over the entire surface.

[0113] <Comparative Example 4> [Manufacturing toner using the pulverization method] ·Crystalline resin A11: 50.0 parts ·Amorphous resin B1: 50.0 parts Fischer-Tropsch wax; melting point 90°C 5.0 parts Colorant Pigment Blue 15:3 9.0 parts The above materials were mixed in a Henschel mixer (FM-75, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 20 s -1 After mixing for 5 minutes, the mixture was kneaded in a twin-screw kneader (PCM-30, Ikegai Corporation) set at 130°C with a screw rotation speed of 250 rpm and a discharge temperature of 130°C. The kneaded mixture was rolled while being cooled using a drum flaker (MBD30-30, Nippon Coke Corporation). The cooling water temperature was set at 15°C, and the conditions were set so that the thickness of the resin composition after rolling and cooling would be 1.0 mm.

[0114] The obtained resin composition was coarsely pulverized to 1 mm or less using a hammer mill to obtain a coarsely pulverized product. The obtained coarsely pulverized product was finely pulverized using a mechanical pulverizer (T-250, manufactured by Freund Turbo Corporation). It was further classified using Faculty F-300 (manufactured by Hosokawa Micron Corporation) to obtain comparative toner particles 4. The operating conditions were a classification rotor rotation speed of 130 s -1 , Dispersion rotor speed 120s -1 It was decided. Furthermore, the same external addition as in Example 1 was carried out to obtain Comparative Toner 4. The physical properties of the toner are shown in Table 3, and the evaluation results are shown in Table 4.

[0115] <Toner Evaluation Method> <1> Low temperature fixability The process cartridges filled with toners 1 to 20 and comparative toners 1 to 5 were left to stand for 48 hours at 25°C and 40% RH. Using an LBP-712Ci (Canon Inc.) modified so that it could operate even without the fixing unit, an unfixed image was printed out with an image pattern in which 9 square images of 10 mm x 10 mm were evenly arranged on the entire transfer paper. The amount of toner on the transfer paper was 0.80 mg / cm. 2 The fixing start temperature was evaluated. The transfer paper was A4 size paper ("Prover Bond paper": 105 g / m 2(manufactured by Fox River) was used. The fixing unit was an external fixing unit that had been removed from the LBP-712Ci and was designed to operate outside the laser beam printer. The fixing temperature of the external fixing unit was raised in 5°C increments from 90°C, and fixing was performed at a process speed of 240mm / sec. The fixed image was visually observed, and the lowest temperature at which no cold offset occurred was defined as the fixing start temperature, and the low-temperature fixing ability was evaluated according to the following criteria. The evaluation results are shown in Table 4. [Evaluation Criteria] A: Fixing start temperature is 100℃ or less B: Fixing start temperature is 105℃ or higher and 110℃ or lower C: Fixing start temperature is 115℃ or higher and 120℃ or lower D: Fixing start temperature exceeds 120°C

[0116] <2> Eraser abrasion resistance of fixed images Using the fixed image at the fixing initiation temperature obtained by the above-mentioned evaluation of low-temperature fixing property, the abrasion resistance was evaluated. 2 The image was rubbed back and forth 15 times with an eraser (PLAST-0120, manufactured by Reufer) with a load of 10 ... ΔD(%)={(image density before rubbing-image density after rubbing) / image density before rubbing}×100 The image density was measured using a color reflection densitometer (X-Rite 404A, manufactured by X-Rite Co., Ltd.). The evaluation results are shown in Table 4. [Evaluation Criteria] A: Concentration reduction rate is less than 3.0% B: Concentration reduction rate is 3.0% or more and less than 5.0% C: Concentration reduction rate is 5.0% or more and less than 10.0% D: Concentration reduction rate is 10.0% or more

[0117] <3> Gross rating the above <1> The images fixed at the fixing start temperature and at a temperature 40°C higher than the fixing start temperature in the evaluation of low-temperature fixability were used. The gloss value was measured using a handy gloss meter PG-1 (manufactured by Nippon Denshoku Industries Co., Ltd.). The measurement conditions were set to 75° for the projection angle and the reception angle, and all image patterns arranged at 9 points were measured and the average value was evaluated. The evaluation results are shown in Table 4. [Gross evaluation criteria] A: The average gross value is 25.0 or more. B: The average gross value is 20.0 or more and less than 25.0 C: Average gross value is 15.0 or more and less than 20.0 D: Average gross value is less than 15.0

[0118] [Table 4]

[0119] The present disclosure relates to the following configurations. (Configuration 1) A toner having toner particles containing a crystalline resin A and an amorphous resin B, The toner has a weight average particle size of 4.0 to 10.0 μm, When the cross section of the toner was observed using a scanning transmission electron microscope, A domain matrix structure in which domains are dispersed in a matrix is ​​observed in the cross section, The matrix contains the crystalline resin A, The domain contains the amorphous resin B, (a) when the domains having a major axis of 300 nm or more are called domains C and the domains having a major axis of 200 nm or less are called domains D, the number-average major axis of the domains D is 30 to 150 nm, (b) The proportion of the cross sections that satisfy both the following (i) and (ii) is 90% or more by number: (i) 5 to 20 domains C are present per cross section of one toner particle, and the area ratio of the domains C is 10 to 30 area % based on the area of ​​the cross section; (ii) the domain D is observed over the entire area of ​​the cross section except for the domain C; A toner characterized by: (Configuration 2) The toner according to Configuration 1, wherein the proportion of the cross sections in which the area ratio of the domain C is 15 to 25 area % based on the area of ​​the cross section is 90% by number or more. (Configuration 3) When the domain C has a major axis of 400 nm or more and is designated as domain E, 3. The toner according to configuration 1 or 2, wherein the proportion of the cross sections in which 4 to 20 domains E exist per toner particle is 90% by number or more. (Configuration 4) The toner according to any one of configurations 1 to 3, wherein the number average major axis of the domains D is 50 to 100 nm. (Configuration 5) The toner according to any one of configurations 1 to 4, wherein the domains D are present in an arbitrary 1 μm square region excluding the domains C in a number of 100 or more. (Configuration 6) The toner according to any one of configurations 1 to 5, wherein the crystalline resin A contains a monomer unit represented by the following formula (1): TIFF2025065738000009.tif48153 In formula (1), R 4 represents a hydrogen atom or a methyl group, and n represents an integer of 15 to 35. (Configuration 7) The toner according to any one of configurations 1 to 6, wherein the crystalline resin A contains a monomer unit having a lactam structure. (Configuration 8) The toner according to any one of configurations 1 to 7, wherein the lactam structure is a five-membered ring lactam structure. (Configuration 9) The toner contains a release agent, The release agent comprises a multifunctional ester wax, The toner according to any one of configurations 1 to 8, wherein the polyfunctional ester wax is at least one ester compound selected from the group consisting of ester compounds of tetravalent to octavalent alcohols and aliphatic monocarboxylic acids, and ester compounds of tetravalent to octavalent carboxylic acids and aliphatic monoalcohols. (Configuration 10) The toner according to Configuration 9, wherein the polyfunctional ester wax is at least one ester compound selected from the group consisting of ester compounds of hexa-octahydric alcohols and aliphatic monocarboxylic acids, and ester compounds of hexa-octahydric carboxylic acids and aliphatic monoalcohols. (Configuration 11) 11. The toner according to any one of configurations 1 to 10, wherein the amorphous resin B has a monomer unit represented by the following formula (2): TIFF2025065738000010.tif49153In formula (2), R 5 represents a hydrogen atom or a methyl group, and m represents an integer of 3 to 35.

Claims

1. A toner having toner particles containing a crystalline resin A and an amorphous resin B, The toner has a weight average particle size of 4.0 to 10.0 μm, When the cross section of the toner was observed using a scanning transmission electron microscope, A domain matrix structure in which domains are dispersed in a matrix is ​​observed in the cross section, The matrix contains the crystalline resin A, The domain contains the amorphous resin B, (a) when the domains having a major axis of 300 nm or more are designated as domains C and the domains having a major axis of 200 nm or less are designated as domains D, the number-average major axis of the domains D is 30 to 150 nm, (b) The proportion of the cross sections satisfying both the following (i) and (ii) is 90% or more by number: (i) 5 to 20 domains C are present per cross section of one toner particle, and the area ratio of the domains C is 10 to 30 area % based on the area of ​​the cross section; (ii) the domain D is observed over the entire surface in the cross section except for the domain C; A toner characterized by:

2. 2. The toner according to claim 1, wherein the proportion of the cross sections in which the area ratio of the domain C is 15 to 25 area % based on the area of ​​the cross section is 90% or more by number.

3. When a domain having a major axis of 400 nm or more among the domains C is designated as a domain E, 3. The toner according to claim 1, wherein the proportion of the cross section in which 4 to 20 domains E exist per one toner particle is 90% by number or more.

4. 3. The toner according to claim 1, wherein the number average major axis of the domains D is from 50 to 100 nm.

5. 3. The toner according to claim 1, wherein the domains D are present in an arbitrary 1 μm square region excluding the domains C in an amount of 100 or more.

6. The toner according to claim 1 , wherein the crystalline resin A contains a monomer unit represented by the following formula (1): In formula (1), R 4 represents a hydrogen atom or a methyl group, and n represents an integer of 15 to 35.

7. The toner according to claim 1 or 2, wherein the crystalline resin A contains a monomer unit having a lactam structure.

8. The toner according to claim 1 or 2, wherein the lactam structure is a five-membered ring lactam structure.

9. The toner contains a release agent, The release agent comprises a multifunctional ester wax, 3. The toner according to claim 1, wherein the polyfunctional ester wax is at least one ester compound selected from the group consisting of ester compounds of tetravalent to octavalent alcohols and aliphatic monocarboxylic acids, and ester compounds of tetravalent to octavalent carboxylic acids and aliphatic monoalcohols.

10. 10. The toner according to claim 9, wherein the polyfunctional ester wax is at least one ester compound selected from the group consisting of ester compounds of hexa-octahydric alcohols and aliphatic monocarboxylic acids, and ester compounds of hexa-octahydric carboxylic acids and aliphatic monoalcohols.

11. The toner according to claim 1 , wherein the amorphous resin B has a monomer unit represented by the following formula (2): In formula (2), R 5 represents a hydrogen atom or a methyl group, and m represents an integer of 3 to 35.

Citation Information

Patent Citations

  • Toner

    JP2014142632A

  • Toner and method for manufacturing toner

    JP2022144501A

  • Toner for electrostatic charge image development

    WO2013047296A1